Associations between human fungiform papillae and responsiveness to oral stimuli: effects of individual variability, population characteristics, and methods for papillae quantification. (27th February 2018) - Piochi, Maria; Dinnella, Caterina; Prescott, John; Monteleone, Erminio
Abstract: Fungiform papillae (FP) on human tongue are the proxy structures designated to oral stimuli detection and transduction. However, the role of their density (fungiform papillae/cm 2 ) in explaining oral sensitivity is still controversial. While early studies generally found that the responsiveness to oral stimuli increased as the number of papillae increased, recent large-scale studies failed to confirm this finding. The present paper reviews relevant studies dealing with the relationship between FP density and responsiveness to oral sensations including: fundamental tastes, 6- n -propyl-2-thiouracil (PROP), and sensations from trigeminal stimulation. Manual methods and automated methods for papillae detection and quantification are reviewed and their advantages and limitations highlighted. The main factors affecting FP density and functionality (age, gender, pathologic impairments) are also considered. Possible bias related to methodological issues in counting technique (equipment used, area and location of the tongue to count, procedures to validate the count), population sample (demographics), and sensory response collection (threshold or supra-threshold stimuli, intensity scaling) are illustrated. The lack of information related to the variability in taste pores density and the possible impairments due to nerve damages, may obscure the relationship between FPD and oral responsiveness.